A tale of two journals or how Elsevier pushed open access in Linguistics - Krämer, Martin; Rooryck, Johan (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. In this talk I provide the background on the transition of a top journal in Linguistics to open access and discuss open access publishing in Linguistics and the problems of this particular transition. The journal Lingua was hosted and marketed by Elsevier which charges substantial subscription fees for its journals and charges authors who want to have their articles published as open access. In the fall of 2015, the editors of the journal wrote a letter to their publishing house Elsevier to express their discomfort with the pricing policy for their journal and asking for a more reasonable policy. Elsevier's reaction to this letter led to the stepping-down of the editors, followed immediately by the complete editorial board. The entire academic Lingua team immediately founded a new journal, Glossa: a journal of general linguistics, which is completely Open Access, published by Ubiquity Press and funded through the Open Library of Humanities. This new foundation was necessary since Elsevier regards Lingua as one of their products and is continuing to publish the journal with a new editorial team. The case received quite some media attention, among others Times Higher Education, Inside Higher Education, The Independent, Slate, and Wired reported. In this talk I will provide the details of the story and discuss commercial and open access publishing in the relatively small field of Linguistics. The conclusion is that it is doable to move even a high profile journal out from behind a huge paywall. Apparently, the Norwegian higher education system isn't quite rigged for this kind of fast change yet if it involves movement of expertise from one label to another rather than movement of the label. While the NSD has approved Glossa this fall, it was granted only the lower level of the system, while Lingua was, and still is, at the top level.